2019
DOI: 10.1111/aje.12639
|View full text |Cite
|
Sign up to set email alerts
|

Human settlement drives African elephant (Loxodonta africana) movement in the Sebungwe Region, Zimbabwe

Abstract: Understanding the key drivers that influence the potential distribution of herbivore species in changing landscapes has been at the centre of enquiry in wildlife science for many decades. This knowledge is particularly important for keystone species like the African elephant (Loxodonta africana) whose population is declining even in conservation areas. The Sebungwe Region is part of the Kavango‐Zambezi Transfrontier Conservation Area and supports ~4,000 elephants. The Sebungwe Region has lost an estimated 76% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The only prevailing model of interaction between elephants and humans (Parker and Graham 1989) proposes that elephant distribution is the inverse of human distribution and that elephant abundance is dependent upon human abundance, based on relative densities at a given scale. This was supported by Mpakairi et al, (2019), who observed that human settlement drives the potential distribution of elephants in the Sebungwe Region (test AUC = 0.95), and patches from the model were on average <1.5 km 2 . This is supported by ranger based knowledge and perception who outlined that recent settlements and encroachment by local communities into the buffer zone could have contributed to elephant decline in SWRA.…”
Section: Human Settlement and Encroachmentsupporting
confidence: 61%
See 4 more Smart Citations
“…The only prevailing model of interaction between elephants and humans (Parker and Graham 1989) proposes that elephant distribution is the inverse of human distribution and that elephant abundance is dependent upon human abundance, based on relative densities at a given scale. This was supported by Mpakairi et al, (2019), who observed that human settlement drives the potential distribution of elephants in the Sebungwe Region (test AUC = 0.95), and patches from the model were on average <1.5 km 2 . This is supported by ranger based knowledge and perception who outlined that recent settlements and encroachment by local communities into the buffer zone could have contributed to elephant decline in SWRA.…”
Section: Human Settlement and Encroachmentsupporting
confidence: 61%
“…Habitat loss through the opening of agricultural lands caused by settlement through the promulgation of statutory instrument 47 of 2014 and illegal hunting in SWRA may disrupt and destroy elephant societies (Mpakairi et al, 2019). In turn, these disruptions can limit the adaptive value of animal social relationships or alter the structure of genetic variation in animal populations and thus resulting in elephant migration and or mortalities which may negatively affect its population (Foley, 2002).…”
Section: Human Settlement and Encroachmentmentioning
confidence: 99%
See 3 more Smart Citations